COLLABORATION IN COMMUNITY EMPOWERMENT INNOVATION FOR ACCELERATING SUSTAINABLE VILLAGE DEVELOPMENT IN SERANG DISTRICT - Muhammad Jaiz; Neka Fitriyah; Ikhsan Ahmad; Asih Kurnianingsih; Abdurohim (PT. Jurnal Center Indonesia Publisher, 2025)
Serang Regency has 326 villages with great agricultural, industrial, and coastal potential, but still faces north-south regional disparities, 18% stunting, and low digital literacy and female participation in the economy. This study examines the effectiveness of innovative pentahelix-based collaboration as a strategy for accelerating sustainable village development in Serang Regency within the framework of the Village SDGs and the 2025-2045 RPJPD vision. The objectives of this study are (1) to analyze the forms and mechanisms of pentahelix collaboration, (2) to evaluate its impact on improving the Village Development Index and achieving Village SDGs, and (3) to formulate concrete policy recommendations for the Serang Regency Government. The benefits of this study include operational guidelines for regional policy makers, replication of the model in similar areas in Banten, and contribution to the national target of independent villages towards Indonesia Emas 2045. The methodology used is descriptive qualitative with a systematic literature review and secondary document analysis. The results show that pentahelix collaboration has succeeded in increasing the average IDM by 18.71%, reducing village poverty by 4.08%, and strengthening the circular economy. Recommendations include allocating 15% of Village Funds for digital platforms and forming a district pentahelix task force.